2018
DOI: 10.3389/fpls.2018.01531
|View full text |Cite
|
Sign up to set email alerts
|

LysM Receptor-Like Kinase and LysM Receptor-Like Protein Families: An Update on Phylogeny and Functional Characterization

Abstract: Members of plant specific families of receptor-like kinases (RLKs) and receptor-like proteins (RLPs), containing 3 extracellular LysMs have been shown to directly bind and/or to be involved in perception of lipo-chitooligosaccharides (LCO), chitooligosaccharides (CO), and peptidoglycan (PGN), three types of GlcNAc-containing molecules produced by microorganisms. These receptors are involved in microorganism perception by plants and can activate different plant responses leading either to symbiosis establishmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
132
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 151 publications
(270 reference statements)
0
132
0
Order By: Relevance
“…So far, the few LysM‐RLKs that have been characterized in different plant species have mostly been linked to roles in recognizing chitin oligomers or lipo‐chitooligosaccharides, but as pointed out by Kawaharada et al (), such proteins have LysM domains that are quite divergent from those of MtLYK10/LjEPR3 homologs. With the notable exception of Arabidopsis thaliana (Buendia et al , ), these MtLYK10/LjEPR3 homologs are widespread in Angiosperms. Interestingly, some dicot species have two copies of this gene as the result of ancient duplications (Figure S6), followed potentially by neofunctionalization or subfunctionalization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, the few LysM‐RLKs that have been characterized in different plant species have mostly been linked to roles in recognizing chitin oligomers or lipo‐chitooligosaccharides, but as pointed out by Kawaharada et al (), such proteins have LysM domains that are quite divergent from those of MtLYK10/LjEPR3 homologs. With the notable exception of Arabidopsis thaliana (Buendia et al , ), these MtLYK10/LjEPR3 homologs are widespread in Angiosperms. Interestingly, some dicot species have two copies of this gene as the result of ancient duplications (Figure S6), followed potentially by neofunctionalization or subfunctionalization.…”
Section: Discussionmentioning
confidence: 99%
“…MtLYK10 homologs were found from Buendia et al () and from NCBI blasts. Synteny was verified using Phytozome (https://phytozome.jgi.doe.gov), SoyBase (https://www.soybase.org) and the Legume Information System, lis (http://legumeinfo.org).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related specifically to effector-triggered immunity, SGT1 exists in four copies (one being unplaced) but only two in the case of S. pennellii and domesticated tomato and there is a dramatic expansion of NLR receptor-encoding genes. Other genes encoding LysM-RLKs, which are typically involved in symbiosis or defense response, depending on species (Buendia et al , 2018) , were expanded in S. lycopersicoides (Solyd02g078930, Solyd09g070440).…”
Section: Functional Annotation and Gene Familiesmentioning
confidence: 99%
“…Some genes involved in the so‐called common symbiosis signalling pathway (CSSP) are required for both RNS and AMS (Gutjahr et al ., ; Bonfante & Genre, ). Phylogenetic analysis of the lysine‐motif (LysM) domain‐containing receptor‐like kinase (LYK) family indicated that the plant perception of mycorrhizal fungal (Myc factor) and rhizobial (Nod factor) lipochitooligosaccharides (LCOs) share the same evolutionary origin (Buendia et al ., ). Overall functional analysis of components of the CSSP supports the current notion that RNS originates from the more ancient AMS (Oldroyd, ).…”
Section: Introductionmentioning
confidence: 97%